Introduction of a prognostic biomarker to strengthen risk stratification of acutely admitted patients: rationale and design of the TRIAGE III cluster randomized interventional trial. Issue 1 (December 2016) - Sandø, Andreas; Schultz, Martin; Eugen-Olsen, Jesper; Rasmussen, Lars; Køber, Lars; Kjøller, Erik; Jensen, Birgitte; Ravn, Lisbet; Lange, Theis; Iversen, Kasper
Abstract Background Several biomarkers have shown to carry prognostic value beyond current triage algorithms and may aid in initial risk stratification of patients in the emergency department (ED). It has yet to be established if information provided by biomarkers can be used to prevent serious complications or deaths. Our aim is to determine whether measurement of the blood level of the biomarkersoluble urokinase plasminogen activator receptor (suPAR) can enhance early risk stratification leading to reduced mortality, lower rate of complications, and improved patient flow in acutely admitted adult patients at the ED. The main hypothesis is that the availability of suPAR can reduce all-cause mortality, assessed at least 10 months after admission, by drawing attention towards patients with an unrecognized high risk, leading to improved diagnostics and treatment. Methods The study is designed as a cross-over cluster randomized interventional trial. SuPAR is measured within 2 h after admission and immediately reported to the treating physicians in the ED. All ED physicians are educated in the prognostic capabilities of suPAR prior to the inclusion period. The inclusion period began January 11th 2016 and ends June 6th 2016. The study aims to include 10.000 patients in both the interventional and control arm. The results will be presented in 2017. Discussion The present article aims to describe the design and rationale of the TRIAGE III study that will investigate whether the availability of prognostic information can improve outcome in acutely admitted patients. This might have an impact on health care organization and decision-making. Trial registration The trial is registered at clinicaltrials.gov (IDNCT02643459, November 13, 2015) and at the Danish Data Protection agency (ID HGH-2015-042 I-Suite no. 04087).